Improving the Channel Utilization of Basic Safety Message in VANETs with Superposition Coded Modulation - Xiang Li; Chao Wang; Fuqiang Liu; Xiaobo Yin (Universitas Ahmad Dahlan, 2016)
In this paper, we propose a broadcast scheme to effectively utilize the scarce and shared wireless medium for vehicular ad-hoc networks (VANETs). By using superposition coded modulation (SCM), information elements that comprise basic safety messages (BSMs) were delivered with different service qualities determined by real-time traffic situations. The optimal power allocation strategy and achievable performance gain of the proposed method were first theoretically analyzed. To apply the proposed method into practice, the hierarchical quadrature amplitude modulation technology was then employed to implement the proposed SCM-based broadcast scheme for VANETs. To evaluate the performance of the proposed method in real-time traffic environments, a joint traffic-communication simulation was further conducted. Results agree that the proposed method extends the coverage of the BSM broadcast while maintaining an acceptable communication reliability to meet the requirement of driving safety.